Comprehensive Profiling of Ethylene Response Factor Expression Identifies Ripening-Associated ERF Genes and Their Link to Key Regulators of Fruit Ripening in Tomato. Issue 3 (6th January 2016) - Liu, Mingchun; Gomes, Bruna Lima; Mila, Isabelle; Purgatto, Eduardo; Peres, Lázaro E.P.; Frasse, Pierre; Maza, Elie; Zouine, Mohamed; Roustan, Jean-Paul; Bouzayen, Mondher; Pirrello, Julien
Abstract : A small subset of ethylene response factor genes emerge as main actors in controlling fruit ripening via both ethylene-dependent and RIN/NOR-mediated mechanisms. Abstract: Our knowledge of the factors mediating ethylene-dependent ripening of climacteric fruit remains limited. The transcription of ethylene-regulated genes is mediated by ethylene response factors (ERFs), but mutants providing information on the specific role of the ERFs in fruit ripening are still lacking, likely due to functional redundancy among this large multigene family of transcription factors. We present here a comprehensive expression profiling of tomato ( Solanum lycopersicum ) ERFs in wild-type and tomato ripening-impaired tomato mutants ( Never-ripe [ Nr ], ripening-inhibitor [ rin ], and non-ripening [ nor ]), indicating that out of the 77 ERFs present in the tomato genome, 27 show enhanced expression at the onset of ripening while 28 display a ripening-associated decrease in expression, suggesting that different ERFs may have contrasting roles in fruit ripening. Among the 19 ERFs exhibiting the most consistent up-regulation during ripening, the expression of 11 ERFs is strongly down-regulated in rin, nor, and Nr tomato ripening mutants, while only three are consistently up-regulated. Members of subclass E, SlERF.E1, SlERF.E2, and SlERF.E4, show dramatic down-regulation in the ripening mutants, suggesting that their expression might be instrumental in fruit ripening. This study illustrates the high complexity of the regulatory network connecting RIN and ERFs and identifies subclass E members as the most active ERFs in ethylene- and RIN/NOR-dependent ripening.